2015
DOI: 10.1073/pnas.1415657112
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ground state and orbital anisotropy in heavy fermion materials

Abstract: The interplay of structural, orbital, charge, and spin degrees of freedom is at the heart of many emergent phenomena, including superconductivity. Unraveling the underlying forces of such novel phases is a great challenge because it not only requires understanding each of these degrees of freedom, it also involves accounting for the interplay between them. Cerium-based heavy fermion compounds are an ideal playground for investigating these interdependencies, and we present evidence for a correlation between or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 47 publications
5
51
0
Order By: Relevance
“…It has been shown that the analysis of the LD effects using the ligand field multiplet (LFM) model gives a good quantitative description of the CEF ground state 26,[28][29][30] . In CeAgSb 2 , the CEF splitting energies from the ground state to the first and second excited states (∆ 1 and ∆ 2 ) have been determined to be 5.2 meV (≈60 K) and 12.5 meV (≈145 K) from the INS measurements, in which the CEF ground state is |±1/2 and the first and second exited levels are dominated by |±3/2 and |±5/2 , respectively 8 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the analysis of the LD effects using the ligand field multiplet (LFM) model gives a good quantitative description of the CEF ground state 26,[28][29][30] . In CeAgSb 2 , the CEF splitting energies from the ground state to the first and second excited states (∆ 1 and ∆ 2 ) have been determined to be 5.2 meV (≈60 K) and 12.5 meV (≈145 K) from the INS measurements, in which the CEF ground state is |±1/2 and the first and second exited levels are dominated by |±3/2 and |±5/2 , respectively 8 .…”
Section: Resultsmentioning
confidence: 99%
“…In tetragonal materials, such as the related material CeRhIn 5 , the orbital character of the 4f wavefunctions can also be manipulated as a function of doping or pressure. 24 As seen in this high field study, the exchange interactions can vary significantly, and even change sign, as the orbital character changes (see Supplementary Information). The ability to produce a simple model capturing the consequences of strong spin-orbit coupling and varying crystal electric fields in the prototypical heavy fermion CeIn 3 is an important step toward a microscopic understanding that couples the spin degrees of freedom to the conduction electrons leading to unconventional quantum critical and superconducting states in f-electron systems.…”
Section: Discussionmentioning
confidence: 65%
“…These simulations were obtained from full atomic multiplet calculations as implemented in the Quanty Package [26,27]. To obtain the best match between calculated and experimental isotropic spectra, the f f (df ) Slater Integrals were reduced by 42.5% (17.5%) from their respective Hartree-Fock values, well in accordance with previous work [7,9,11,14,28]. In addition, the Ce 3d core hole spin orbit coupling constant ζ 3d was slightly readjusted to reproduce the experimental separation between the M 4 and M 5 edges.…”
mentioning
confidence: 89%
“…In a solid environment, the degeneracy of the rare earth 4f ground configuration is lifted by the crystal field in general, causing both an anisotropic 4f charge distribution and, in conjunction with spin orbit coupling, (single ion) magnetic anisotropy. Unraveling the crystal field induced level structure thus constitutes an essential part of understanding the low temperature physics and of establishing correlations between local 4f symmetry at low temperature on the one hand and macroscopic ground state properties on the other.In this respect, the usefulness of probing the 4f configuration with linear polarized soft x-rays [6] has been demonstrated for a variety of Ce compounds in recent years [7][8][9][10][11][12][13][14], allowing to settle several open issues, where other experiments left room for diverging interpretations. Its magnetic variants, x-ray magnetic linear and circular dichroism (XMLD, XMCD) constitute sensitive element and orbital specific probes of magnetic polarization and anisotropy [15][16][17][18][19][20].…”
mentioning
confidence: 99%